2021
DOI: 10.1021/acsami.1c05129
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening in Metal/Graphene Composites: Capturing the Transition from Interface to Precipitate Hardening

Abstract: A promising materials engineering method for improving the strength of crystalline materials is to add obstacles to dislocation motion that induce interface hardening (IH) or precipitate hardening (PH). In this study, molecular dynamics simulations are performed for Ni/graphene composites, revealing for the first time that graphene can strengthen the Ni matrix not only strictly via IH or PH but also through a continuous transition between the two. When graphene behaves like an interface, dislocation pileups fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In our case, dislocation absorption predominates. Several studies 45,46 also support the occurrence of dislocation absorption-induced hardness reduction, even when graphene reinforcement is predominant. In addition, this phenomenon might be influenced by the crystal type of the composite material.…”
Section: Multiple Factors Affecting Hardness Of Composite Materialsmentioning
confidence: 85%
“…In our case, dislocation absorption predominates. Several studies 45,46 also support the occurrence of dislocation absorption-induced hardness reduction, even when graphene reinforcement is predominant. In addition, this phenomenon might be influenced by the crystal type of the composite material.…”
Section: Multiple Factors Affecting Hardness Of Composite Materialsmentioning
confidence: 85%
“…In addition, the degree of graphene dispersion is higher and more uniform at low temperature rolling. Fei [ 39 , 40 , 41 ] and Zhao [ 14 , 42 ] et al found that graphene has a hindering effect on the movement of dislocations in the metal matrix. When the degree of graphene dispersion is higher, the locking effect on dislocations is more obvious, which also contributes more to the hardness enhancement of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the nanopillars were compressed along the z -axis by a virtual rigid plane at a rate of 12 m/s under the canonical (NVT) ensemble. Notably, such a virtual plane was realized by the repulsive force model, as shown in Equation ( 2 ), which has been extensively employed in previous studies [ 19 , 35 , 43 ]. For comparison, the pure HEA nanopillar was compressed under the same simulation conditions.…”
Section: Methodsmentioning
confidence: 99%